IMMUNOMODULATORY ACTIVITY OF MUNTINGIA CALABURA L. FRUITS USING CARBON CLEARANCE ASSAY AND THEIR TOTAL FLAVONOID AND PHENOLIC CONTENTS - SUJONO, TANTI AZIZAH; DIAN KUSUMOWATI, IKA TRISHARYANTI; MUNAWAROH, RIMA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: Muntingia calabura L fruits have several advantages for health and can be consumed as alternative medicine. This study aims to evaluate the immunomodulatory activity of methanol extract (ME) and fractions of M. calabura L fruits against non-specific immune response in mice and its total phenolic and flavonoid contents. Methods: This research using carbon clearance assay or phagocytosis method which was done on mice. Seventy male Swiss mice were divided into 14 groups. Mice were treated with ME, hexane fraction (HF), dichloromethane fraction (DF), and ethyl acetate fraction (EAF) of M. calabura L. orally at a dose of 50, 100, and 200 mg/kg daily for 7 days. Zymosan with a dose of 15 mg/kg was used as a positive control and given intraperitoneally, and CMC Na was used as a negative control. On the 8th day, mice were injected with carbon ink suspension intravenously and blood samples were taken at the minutes of 0, 5, 10, 15, 20, and 30. Furthermore, the transmittance was measured at λ 675 nm. The total phenolic content was measured using the Folin–Ciocalteu method, and flavonoid content was measured using the AlCl3 method. Results: Zymosan, ME, and EAF of M. calabura L. at a dose of 200 mg/kg showed a strong immunostimulatory effect (phagocytic index >1.5) while the HF and DF groups showed that the higher doses decreased the phagocytic index. The total phenolic contents of ME, HF, DF, and EAF were 27.90, 11.11, 16.72, and 30.11%, respectively, while the flavonoid contents were 4.07, 0.17, 3.07, and 1.86%, respectively. Conclusion: ME and EAF of M. calabura L. fruits have immunostimulatory activity.